One Hospital's Timeline for In-Hospital Vertical Evacuation during a Flood Disaster. Issue Volume 34:Issue s1(2019) (May 2019) - Iwasaki, Megumi; Shoko, Tomohisa; Akahoshi, Koki; Adachi, Tomohiro; Yoshikawa, Kazuhide
Abstract : Introduction: Recently, the risk of flood disasters due to concentrated heavy rains has been increasing in Japan. While some cases of hospital evacuation have been reported, standards for hospital evacuation have not been established and regional administrative evacuation plans do not include medical facilities. Aim: To clarify the timeline for in-hospital vertical evacuation during a flood disaster. Methods: A timeline was set for vertical evacuation as criteria of the hospital's emergency response based on the Arakawa River Downstream Timeline, which is an estimate of the time until river flooding based on the water level of the Arakawa River located near the facility. The timeline was calculated backward from 0 hours to when the river floods. A drill was held for verification. Results: The timeline was based on the water level of the Arakawa River and objective evidence of risky transfer of critical patients; therefore, the decision to evacuate was made when the water level reached a dangerous level (-3 hours). However, this did not provide enough time to evacuate patients in all hospital departments simultaneously, resulting in a shortage of human resources. There was a planned shutdown of the electronic clinical record system at 0 hours to avoid water damage and evacuation of its server, but three hours were not enough to prepare patient clinical summaries. Discussion: There is a need for greater and earlier preparation for evacuation to reduce or discharge patients who can leave the hospital when a flood disaster is predicted. Only in-hospital vertical evacuation was considered because it is very risky to transfer critical patients without an evacuation order from government or municipal officials. In fact, over 10, 000 patients would need to be evacuated in the region if the Arakawa River floods. Therefore, a regional plan is indispensable for such large scale and simultaneous hospital evacuations.